Sensory and autonomic innervation of the local tissues at traditional acupuncture point locations GB14, ST2 and ST6. Issue 6 (December 2022) - Wang, Jia; Cui, Jing-jing; Xu, Dong-sheng; Su, Yu-xin; Liao, Jie-ying; Wu, Shuang; Zou, Ling; Guo, Ya-ting; Shen, Yi; Bai, Wan-zhu
Objective: To visualize and compare the sensory and autonomic innervation of the local tissues at the sites of different traditional acupuncture points in the rat forehead and face by histochemical examination. Methods: GB14 ( Yangbai ), ST2 ( Sibai ) and ST6 ( Jiache ) were selected as the representative traditional acupuncture points in this study, and the local tissues at these sites were dissected in rats after perfusion followed by double or triple fluorescent histochemical staining. Here, calcitonin gene-related peptide (CGRP), tyrosine hydroxylase (TH) and vesicular acetylcholine transporter (VAChT) were used to label the sensory, sympathetic and parasympathetic nerve fibers, respectively. Results: The CGRP + sensory, TH + sympathetic and VAChT + parasympathetic nerve fibers were simultaneously demonstrated in the local tissues at GB14, ST2 and ST6. Although the three kinds of nerve fibers ran in parallel or intermingled with each other, by the analysis from the view of three-dimensional reconstruction, it was clear that each of them distributed in an independent pattern to their corresponding target tissues including the blood vessels, hair follicles, arrector pili and subcutaneous muscles, as well as sebaceous glands. Conclusion: Our study demonstrated the sensory and autonomic innervation of the local tissues at GB14, ST2 and ST6, providing neurochemical evidence indicating that the CGRP + sensory, TH + sympathetic and VAChT + parasympathetic nerve fibers form a neural network at these point locations that may respond to acupuncture stimulation.